High‐Performance Supercapacitors: In Situ Synthesis of Vertical Standing Nanosized NiO Encapsulated in Graphene as Electrodes for High‐Performance Supercapacitors (Adv. Sci. 3/2018). Issue 3 (25th March 2018) - Lin, Jinghuang; Jia, Henan; Liang, Haoyan; Chen, Shulin; Cai, Yifei; Qi, Junlei; Qu, Chaoqun; Cao, Jian; Fei, Weidong; Feng, Jicai
Abstract : In article number 1700687, Junlei Qi, Jian Cao, and co‐workers report the development of vertical‐standing nanosized NiO encapsulated in graphene as electrodes for high‐performance supercapacitors. The resultant NiO encapsulated in high‐quality graphene layers as electrodes can exhibit a high specific capacity, good rate capability, and excellent cycling performance because of the integrated structures of NiO nanoparticles, the high‐quality graphene layers, and the vertical‐standing nanosheets.